Data-Driven Modeling and Prediction of Complex Spatio-Temporal Dynamics in Excitable Media - Herzog, Sebastian; Wörgötter, Florentin; Parlitz, Ulrich (Frontiers in Applied Mathematics and Statistics, 2018)
Spatio-temporal chaotic dynamics in a two-dimensional excitable medium is (cross-) estimated using a machine learning method based on a convolutional neural network combined with a conditional random field. The performance of this approach is demonstrated using the four variables of the Bueno-Orovio-Fenton-Cherry model describing electrical excitation waves in cardiac tissue. Using temporal sequences of two-dimensional fields representing the values of one or more of the model variables as input the network successfully cross-estimated all variables and provides excellent forecasts when applied iteratively.